Silicon nitride: a potent solid-state bioceramic inactivator of ssRNA viruses - Giuseppe Pezzotti (Nature Portfolio, 2021)
Abstract Surface inactivation of human microbial pathogens has a long history. The Smith Papyrus (2600 ~ 2200 B.C.) described the use of copper surfaces to sterilize chest wounds and drinking water. Brass and bronze on doorknobs can discourage microbial spread in hospitals, and metal-base surface coatings are used in hygiene-sensitive environments, both as inactivators and modulators of cellular immunity. A limitation of these approaches is that the reactive oxygen radicals (ROS) generated at metal surfaces also damage human cells by oxidizing their proteins and lipids. Silicon nitride (Si3N4) is a non-oxide ceramic compound with known surface bacterial resistance. We show here that off-stoichiometric reactions at Si3N4 surfaces are also capable of inactivating different types of single-stranded RNA (ssRNA) viruses independent of whether their structure presents an envelop or not. The antiviral property of Si3N4 derives from a hydrolysis reaction at its surface and the subsequent formation of reactive nitrogen species (RNS) in doses that could be metabolized by mammalian cells but are lethal to pathogens. Real-time reverse transcription (RT)-polymerase chain reaction (PCR) tests of viral RNA and in situ Raman spectroscopy suggested that the products of Si3N4 hydrolysis directly react with viral proteins and RNA. Si3N4 may have a role in controlling human epidemics related to ssRNA mutant viruses.